2005
DOI: 10.1016/j.jsp.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship influences on teachers' perceptions of academic competence in academically at-risk minority and majority first grade students

Abstract: This study examined the associations among child demographic variables, teacher perceptions of parent-teacher and student-teacher relationship quality, and teacher perceptions of children's academic abilities in an ethnically diverse sample of 607 academically at-risk first grade children. Relative to relationships with African American children and parents, teachers rated their relationships with White and Hispanic children and parents more positively. Measures of relationship quality added unique variance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
172
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(197 citation statements)
references
References 51 publications
(81 reference statements)
12
172
2
4
Order By: Relevance
“…Although several researchers have pointed to a gap in knowledge on the relationship among teacher expectations and student attributes other than their demographic background (Hecht and Greenfield 2002;Hughes et al 2005; Rubie-Davies 2010), a lack of empirical evidence remains. The aim of the present study was to contribute to knowledge on the issue why for some students the expectations of teachers do not correspond with students' performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although several researchers have pointed to a gap in knowledge on the relationship among teacher expectations and student attributes other than their demographic background (Hecht and Greenfield 2002;Hughes et al 2005; Rubie-Davies 2010), a lack of empirical evidence remains. The aim of the present study was to contribute to knowledge on the issue why for some students the expectations of teachers do not correspond with students' performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A plausible explanation for this finding is that engaged students tend to be more compliant and exhibit appropriate classroom behavior, which may have contributed to their teachers' positive assessments and expectations (Rubie-Davies 2008). Finally, it has been found that the quality of the student-teacher relationship, as perceived by the teacher, is more closely related to teachers' expectations than the children's measured performance and background (Hughes et al 2005;RubieDavies 2010). Teachers had higher expectations of academic performance for students for whom they perceived a more positive student-teacher relationship.…”
Section: Teacher Perceptions Of Student Attributes and Expectationsmentioning
confidence: 99%
See 3 more Smart Citations